The Perception of The Widow in Stand-up Comedy Mega Syalshabillah - Sihombing, Lambok Hermanto; Saputra, Adithiya Wiradinatha (Lingual Journal of Language and Culture; Vol 13 No 1 (2022): Lingual: Journal of Language and Culture, 2022)
This article discusses the perception of widows in the stand-up comedy presented by Mega Syalshabillah. Stand-up comedy is a comedy performance art performed by one performer or who is familiarly called a comic. In her performances, Mega Syalshabillah always uses a theme close to the life of a widow. The depiction she did was a form of answering the negative perception that existed in the public's mind about a widow. In this study, the author will examine how the perception of widows in stand-up comedy delivered by Mega Syalshabillah. Researchers use data sourced from YouTube shows, and this is because the YouTube platform is very close and dominantly used as a means of finding information/watching entertainment by the public. The process for selecting YouTube views is based on the most significant number of views. In practice, the author uses the theory of perception proposed by J. Cohen. The theory of perception that the researcher used aims to see the views and perspectives of a widow due to divorce. Personal branding theory is also used in this study as a supporting theory, and it aims to answer how a comedian promotes himself so that the wider community knows it. The findings obtained from this analysis are that people always have a negative perception of a widow due to divorce; the community first generalizes the bad things about widow status.